The Influence of Word of Mouth Marketing Regarding The Decision to Purchase Services From PT. JILC Pongtiku Branch in Makassar City - Budiman, Amin (Economics and Business Journal (ECBIS), 2024)
This research aims to determine the marketing influence of Word of Mouth Marketing on the decision to purchase services from PT. JILC Branch My Pongti in Makassar City. The population in this research is JILC students My group is 252 people. The number of samples used was 71 people by using Slovin's sample theory. Data collection was carried out by using observation and questionnaire methods. Technical data analysis used is multiple linear regression analysis using statistics Product and Service Solution (SPSS) v.21. The multiple linear regression equation produces the equation Y = 5.451 + 0.697X1 + 0.052X2. Thus the results of this study found that The Word of Mouth variable has a positive and significant effect on decisions Consumer. The results of the correlation analysis of determination (R Square) were 0.487 or 48.7%. This shows that the percentage influence of the independent variable amounting to 48.7%. Meanwhile, the remaining 51.3% was influenced or explained by other variables not included in this research model. F count (32.327)> F table (3.128) with a significance level of 0.000 < 0.05. So hypothesis that is accepted is H1 which means variable X (Organic WOM and Amplified WOM) simultaneously has a significant influence on variable Y (Consumer Decision). Meanwhile, the t test results explain the calculated t for variable X1 is (7.185) > t table (1.995) with a significance level of 0.000 < 0.05. So H0 is rejected and the accepted hypothesis is H2 which means variable Organic WOM partially has a significant influence on the variables Y (Consumer Decision). The results of the partial test for variable X2 explain that t count 0.0494 > 0.05. So H3 is rejected and the accepted hypothesis is H0 which means that the Amplified WOM variable partially has no influence significant to variable Y (Consumer Decision).